The effect of liquidity, profitability, sales growth, and dividend policy on stock prices after the implementation of IFRS - Dany Pranata; Diyah Pujiati (STIE Perbanas Surabaya, 2015)
The objective of this research is to find out the effect of liquidity (CR), profitability (ROA), sales growth (SG), and dividend policy (DPR) on the stock price after the implementation of IFRS. This is a quantitative research with the samples consisting of 13 companies of the 45 companies listed on LQ45 in Indonesia Stock Exchange (IDX) during 2011-2013. Totally, there were 39 data collected for the analysis. The sample was determined using purposive sampling method. The data were analyzed by using multiple linear regression analysis. The result provides evidence that lead to a conclu-sion. Therefore, it can be concluded that, partially, the variables of Current Ratio (CR), Return on Assets (ROA), sales growth (SG), and Dividend Payout Ratio (DPR) have an effect on stock prices. In addition, Current Ratio (CR), Return on Assets (ROA), and Dividend Payout Ratio (DPR) simultaneously have a significant effect on stock prices. However, the sales growth (SG) has no significant effect on stock prices.